Applying participatory climate risk and livelihoods mapping to define users’ demand for climate services - Barlis, Angelica; Palao, Leo Kris; Vu Huong, Ngan; Kim, Kwang Hyung; Soksophors, Yim; Phanna, Khieng; Burja, Kurt; Scholz, Benjamin; Swaans, Cornelis P.M. (DeRISK SE Asia, 2022)
This brief presents how a participatory approach in livelihood mapping was applied to define the need for climate services in key cropping systems within major livelihoods. This process was built upon the existing product developed by the World Food Programme (WFP) in Cambodia called Consolidated Livelihoods Exercise for Analyzing Resilience (CLEAR) maps.